PEMERIKSAAN IBU HAMIL DAN PEMERIKSAAN TT GRATIS DI PUSKESMAS BANGKALAN - Novi Anggraeni; Dwi Wahyung tiyas (STIKES NGUDIA HUSADA MADURA, 2019)
One of the disorders of pregnancy that can occur in pregnant women, fetuses and after childbirth is tetanus infection. Tetanus is an acute and sometimes fatal infectious disease caused by neorotoxin (tetanuspasmin) produced from clostridium tetani, whose spores enter the body through wounds. Based on data from the World Health Organization (WHO) worldwide, the Maternal Mortality Rate (MMR) during childbirth, there are 500,000 maternal deaths per year and 10,000,000 neonatal deaths per year. Indonesia has implemented the Development of the Immunization Program (PPI) since 1977 with the aim of including the Elimination of Neonatal Tetanus (ETN) with the aim of reducing the incidence of neonatal tetanus to 1 / 10,000 live births (Ditjen PP & PL, 2012). Based on a survey through interviews with mothers information about pregnant women at the Bangkalan Community Health Center that has been carried out is that there are still many pregnant women at the Bangkalan Community Health Center who do not yet know the importance of TT examination. The method used to carry out community service is by collecting data on the number of pregnant women at the Bangkalan Community Health Center. Then conduct interviews with mothers about the understanding of antenatal care, and TT examination. Then make a time contract with pregnant women. The activity was continued with training for free Pregnancy Check-Up and TT injection held at the Bangkalan Community Health Center. Participants in the activity were 35 pregnant women at the Bangkalan Community Health Center who participated in the training and free TT injection. While participating in the activity, the mother was very enthusiastic about the material presented. She was also able to ask questions related to the material presented. The results of the activity showed that most of the mothers' knowledge was 21 mothers (60%) and the mother's TT immunization status was incomplete, namely 20 mothers (57.1%).